Facing War: Rethinking Europe's Security and Defence - Giusti, Serena (ISPI Publications, 2022)
Russia's attack on Ukraine has sent shockwaves across Europe and the world. While the current war is a geopolitical turning point, it remains unclear whether it will trigger a quantum leap forward for European defence policies and for the role of the European Union as a security provider. This Report investigates whether we can expect a further convergence of European strategic cultures, and on collaboration among Europeans to generate the required military capabilities and integrate their forces. Most importantly, it finds that the timely implementation of the EU's Strategic Compass will be a decisive test to establish whether Europeans are rising to the challenge of taking more responsibility for their security and defence.